2008
DOI: 10.1007/s00213-008-1212-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in pre- and postsynaptic 5-HT1A receptor function and cocaine supersensitivity in serotonin transporter knockout rats

Abstract: Rationale While individual differences in vulnerability to psychostimulants have been largely attributed to dopaminergic neurotransmission, the role of serotonin is not fully understood. Objectives To study the rewarding and motivational properties of cocaine in the serotonin transporter knockout (SERT −/− ) rat and the involvement of compensatory changes in 5-HT 1A receptor function are the objectives of the study. Materials and methodsThe SERT −/− rat was tested for cocaine-induced locomotor activity, cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 58 publications
9
81
4
Order By: Relevance
“…Roberts et al (1994) reported increased breakpoints for cocaine in a progressive-ratio schedule of reinforcement following global depletion of 5-HT in the brain (see also : Loh and Roberts 1990). This view is also supported by a recent study in serotonin transporter knockout rats, which showed enhanced cocaine-induced hyperlocomotion, CPP, as well as enhanced cocaine self-administration (Homberg et al 2008). These findings implicate an increase of the incentive value of cocaine and, therefore, would suggest that 5-HT has an inhibitory role in cocaine-mediated reinforcement.…”
Section: Discussionmentioning
confidence: 59%
“…Roberts et al (1994) reported increased breakpoints for cocaine in a progressive-ratio schedule of reinforcement following global depletion of 5-HT in the brain (see also : Loh and Roberts 1990). This view is also supported by a recent study in serotonin transporter knockout rats, which showed enhanced cocaine-induced hyperlocomotion, CPP, as well as enhanced cocaine self-administration (Homberg et al 2008). These findings implicate an increase of the incentive value of cocaine and, therefore, would suggest that 5-HT has an inhibitory role in cocaine-mediated reinforcement.…”
Section: Discussionmentioning
confidence: 59%
“…However, depending on the behavioral effect of cocaine, enhanced NE and 5-HT release (upon blockade of NET and SERT) may also play a role (Drouin et al, 2002;Homberg et al, 2008;Hall et al, 2009 Since an inhibitory effect of insulin on electrically evoked monoamine release in brain slices was associated with potentiation of the release-enhancing effect of monoamine transporter blockers, our study reveals that insulin presynaptically enhances the function of monoamine transporters in frontal cortical and striatal rat brain regions.…”
mentioning
confidence: 75%
“…In agreement with the large literature implicating 5-HT in the pathophysiology and treatment of mood and anxiety disorders, SERT-deficient (−/− and +/-) mice showed an anxiogenic phenotype, which was ameliorated by a 5-HT1A antagonist (215, 220, 228, 229). Cognitive assays showed SERT−/− rodents may perform better in emotionally guided/motivated learning, but worse in “neutral” tasks - perhaps related to the anxiety-like phenotype (230, 231). Consistently, a SERT-overexpressing mouse line showed a phenotype opposite to the SERT−/− in many respects: reduced extracellular and total 5-HT levels, and decreased anxiety-like behaviors (232, 233).…”
Section: Animal Geneticsmentioning
confidence: 99%